Ohjelmistotestauksen lopetuskriteerit: systemaattinen kirjallisuuskatsaus - Weckberg, Siiri (2025)
Software testing aims to validate various requirements of the software and verify its functionality, ensuring its quality. In theory, software can be tested indefinitely but in practice testing is limited by the resources available. For this reason termination criteria are defined for software testing conditions that must be met for the testing process to be considered complete. This study conducted a systematic literature review to examine the termination criteria used in the IT industry and termination criteria proposed in research. Only six studies were included in the review, making it impossible to derive a generalizable answer to the research questions. The findings indicate that little research has been conducted on software testing termination criteria. The benefits of using termination criteria found in the literature include saving money, time and environmental resources. Therefore further research on this topic is importantand the thesis proposes opportunities for further research. The need for further research is also supported by previous studies.